The development of Trichostrongylus colubriformis larvae on a range of herbage species or on plots of differing topographical aspect - Niezen, J.H.; Robertson, H.A.; Miller, C.M.; Hay, F.S. (Elsevier, 2003)
Five "contaminations", where faeces containing Trichostrongylus colubriformis eggs were deposited on pasture and serially recovered, were used to compare the rate of decline of faecal mass and larval development. In the first three contaminations, faeces from a common source were deposited on swards of browntop (Agrostis capillaris cv Grasslands Muster), ryegrass (Lolium perenne cv Grassland Nui), white clover (Trifolium pratense cv Grassland Tahora), or onto bare ground in the late spring, summer or autumn. The last two contaminations were done on the north facing aspect or south facing aspect of hill country pastures in summer and autumn. Number of free-living nematodes (first- and second-stage larvae (L1 and L2) and soil dwelling nematodes) and third stage larvae (L3) recovered from faeces were counted. In spring there was a significant (P<0.01) effect of sward type on the mass of faeces remaining, with greatest mass remaining on browntop and ryegrass 28 days later, and less on bare ground and white clover. In summer there were more (P<0.05) faeces remaining on browntop than on other herbages which had little faeces remaining and which did not differ one from another. In autumn there was a rapid decline in faecal mass. All faeces were gone from white clover and ryegrass swards by day 10 and from browntop and bare ground by day 14. The number of free-living nematodes did not differ markedly between seasons, ranging from 5 to 8.5% of eggs deposited. The number of L3 recovered was low in spring (?0.4% of eggs deposited) and did not differ between swards. In summer, more (P<0.05) L3 were recovered from faeces deposited on swards of ryegrass and white clover than from bare ground or browntop. Most L3 were recovered from days 7 to 14 (?1.3% of eggs deposited). In the autumn, low numbers of L3 were recovered from browntop on day 3 and ryegrass on day 7 (0.2% of eggs deposited) with virtually no L3 recovered from faeces placed on white clover or bare ground. There were significant (P<0.001) effects of aspect on the amount of faecal mass remaining in both summer and autumn with less faeces remaining on the south facing aspect than on the north. This was particularly evident during the summer when virtually all of the faeces were intact on the north facing aspect but only 40% was remaining on the south on day 28. In the autumn, while faeces were completely gone from both aspects by day 28 but there were less (P<0.05) faeces remaining on the south facing aspect from days 3 to 18 than from the north. There was no aspect effect in either season on the number of free-living nematodes recovered which averaged 8-11% of eggs deposited. In both seasons a greater number of L3 were recovered from faeces on the south facing aspect than on the north, particularly 3-10 days after faecal deposition. In summer the rise in L3 recovered in faeces was more rapid on south facing aspect than on the north but both attained a maximum level of ?4% of eggs deposited. In autumn on day 3 there was a rapid rise on south facing aspect to ?21% of eggs deposited followed by a gradual decline on day 10 while on the north facing aspect numbers of L3 recovered only attained 10% of eggs deposited.